The N.Y. Hotel: a 5-star hotel development in Barangay Ugong, Pasig City - De Leon, Jane Esi C., Japzon, Joaquin Andres L., Jose, Sarjay Alain D., Lagne, Allen Jay P. 4 0 16; 5 (2024)
u
Feasibility Study: (Bachelor of Science in Real Estate Management) - Pamantasan ng Lungsod ng Maynila, 2024.
Keywords: 2 -- 0; 6; 20; 20; 2